The Emerald handbook of narrative criminology - Fleetwood, Jennifer; Presser, Lois; Sandberg, Sveinung; Ugelvik, Thomas (Emerald Publishing Limited, 2019)
Narrative criminology is an approach to studying crime and other harm that puts stories first. It investigates how such stories are composed, when and why they are told and what their effects are. This edited collection explores the methodological challenges of analysing offenders' stories, but pushes the boundaries of the field to consider the narratives of victims, bystanders and criminal justice professionals.This Handbook reflects the diversity of methodological approaches employed in narrative criminology. Chapters discuss the practicalities of listening to and observing narratives through ethnographic and observational research, and offer accessible guides to using diverse methodological approaches for listening to and interpreting narrative data.With contributions from established and emerging scholars from all over the world, and from diverse fields including politics, psychology, sociology and criminology, the Handbook reflects the cutting edge of narrative methodologies for understanding crime, control and victimisation and is an essential resource for academics studying and teaching on narrative criminology.